The Relationship Between Gratitude and Resilience in Correctional Inmates in Class I Correctional Institution in Makassar - Syahid, Andi Ali; Tetteng, Basti (Polteknik Ilmu Pemasyarakatan, 2024)
Gratitude that is owned in individuals, can generate resilience in individuals. Also, low gratitude will not generate resilience in individuals who experience problems. Conversely, if gratitude is high then resilience will also rise. This study aims to determine whether gratitude has a relationship with resilience in prison-assisted residents in Makassar Class 1 Correctional Institutions. Participants in this study amounted to 288 people with the sampling technique used was cluster random sampling. The hypothesis test used is the spearman correlation analysis technique. The results of the test obtained sig p = (0.001) < 0.005 and r = (0.202) then gratitude contributed 4% to resilience or r² = 0.040. So it can be concluded that gratitude and resilience have a positive relationship so that when individuals have high gratitude, the resilience they have will also be high in correctional facilities at Makassar Class 1 Correctional Institution. The implication in this study is that gratitude can be used for interventions to increase resilience in correctional assisted citizens.